1972
DOI: 10.1159/000301751
|View full text |Cite
|
Sign up to set email alerts
|

A Critique on the Evaluation and Mode of Action of Antiestrogens

Abstract: (1) The ‘true antiestrogens’ are estrogenic and are competitive inhibitors of estrogen action at the estrogen-sensitive target organs. The estrogenicity of a compound needs to be specified with reference to (a) the target tissue, (b) parameter used, (c) route of administration, (d) dose of the compound, (e) time sequence of action. The degree of antiestrogenicity is directly proportional to the, estrogenicity of the compound. The antiestrogenic action of a compound is related to its affinity with the receptor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1974
1974
1994
1994

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Sankaran and Prasad (1972) have reported that glycogen synthesis is initiated in the uterus of immature rats when exogenous oestrogen is administered. The present findings clearly reveal that in the uterus of immature rats there is no glycogen, however, when the hexane extract is administered orally, glycogen appeared in the uterus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sankaran and Prasad (1972) have reported that glycogen synthesis is initiated in the uterus of immature rats when exogenous oestrogen is administered. The present findings clearly reveal that in the uterus of immature rats there is no glycogen, however, when the hexane extract is administered orally, glycogen appeared in the uterus.…”
Section: Discussionmentioning
confidence: 99%
“…Of the various biochemical constituents in the uterus, glycogen plays an important role in adult rats for performing various reproductive functions (Shelesnyak et al, 1963;Saldarini and Yochim, 1968;Demers et al, 1972), however, glycogen is not present in the uterus of immature rats. Sankaran and Prasad (1972) have reported that glycogen synthesis is initiated in the uterus of immature rats when exogenous oestrogen is administered. The present findings clearly reveal that in the uterus of immature rats there is no glycogen, however, when the hexane extract is administered orally, glycogen appeared in the uterus.…”
Section: Discussionmentioning
confidence: 99%